2010
DOI: 10.1002/kin.20468
|View full text |Cite
|
Sign up to set email alerts
|

Shock tube study of 1,3,5‐triazine dissociation and relaxation and relaxation of pyrazine

Abstract: The three-body dissociation of 1,3,5-triazine (s-triazine, s-C 3 H 3 N 3 → 3HCN) has been observed in incident shock waves with the laser-schlieren technique. The experiments use 5% triazine/Kr and cover 1630-2350 K for 100-600 Torr. These experiments show dissociation rates with strong falloff and a slight but fully expected pressure dependence. The dissociation is without secondary reaction save for a possible, but rather unlikely, contribution from the isomerization HCN → HNC. Electronic structure calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…There has been increasing interest in understanding the pyrolysis of nitrogen-containing heterocycles, especially five-membered (azole) and six-membered (azine) compounds. These nitrogen-rich species are abundant in coal , and represent the fundamental unit of many high-energy-density materials. , Combustion of these compounds leads to the production of nitrogen oxide (NO x ) species, which play an important role in the formation and degradation of tropospheric ozone . A number of studies have focused on the pyrolysis of azine molecules containing one, two, and three nitrogen atoms (referred to as pyridine, diazines, and triazines, respectively). One of the main goals of these studies was to determine the strength and reactivity of specific C–H bonds that were shown to be critical in the decomposition process. For example, the generally accepted mechanism for decomposition of pyridine is initiated by the cleavage of the weakest C–H bondthe bond adjacent to the nitrogen atom .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing interest in understanding the pyrolysis of nitrogen-containing heterocycles, especially five-membered (azole) and six-membered (azine) compounds. These nitrogen-rich species are abundant in coal , and represent the fundamental unit of many high-energy-density materials. , Combustion of these compounds leads to the production of nitrogen oxide (NO x ) species, which play an important role in the formation and degradation of tropospheric ozone . A number of studies have focused on the pyrolysis of azine molecules containing one, two, and three nitrogen atoms (referred to as pyridine, diazines, and triazines, respectively). One of the main goals of these studies was to determine the strength and reactivity of specific C–H bonds that were shown to be critical in the decomposition process. For example, the generally accepted mechanism for decomposition of pyridine is initiated by the cleavage of the weakest C–H bondthe bond adjacent to the nitrogen atom .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental bond strength values provide data points with which theoreticians can compare their models. However, few experimental studies of gaseous azines exist, and they have been largely limited to shock tube experiments that rely on complex modeling of the data, resulting in fairly large error bars. ,,, Moreover, to date there are no experimental determinations of the BDEs of 1,2-diazine or any triazines. The experimental shock tube results were later complemented by a comprehensive theoretical investigation by Barckholtz et al focused on computing the C–H and N–H BDEs of aromatic hydrocarbons .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous molecular systems became objects for the study of three-body photodissociation dynamics [10][11][12][13][14]. Among them, acetone [15,16] is probably the best-studies molecule.…”
Section: Introductionmentioning
confidence: 99%